Comparison of different approaches for direct coupling of solid-phase microextraction to mass spectrometry for drugs of abuse analysis in plasma - Wei Zhou; Martyna N. Wieczorek; Runshan Will Jiang; Janusz Pawliszyn (Elsevier, 2023)
The direct coupling of solid-phase microextraction (SPME) to mass spectrometry (MS) (SPME-MS) has proven to be an effective method for the fast screening and quantitative analysis of compounds in complex matrices such as blood and plasma. In recent years, our lab has developed three novel SPME-MS techniques: SPME-microfluidic open interface-MS (SPME-MOI-MS), coated blade spray-MS (CBS-MS), and SPME-probe electrospray ionization-MS (SPME-PESI-MS). The fast and high-throughput nature of these SPME-MS technologies makes them attractive options for point-of-care analysis and anti-doping testing. However, all these three techniques utilize different SPME geometries and were tested with different MS instruments. Lack of comparative data makes it difficult to determine which of these methodologies is the best option for any given application. This work fills this gap by making a comprehensive comparison of these three technologies with different SPME devices including SPME fibers, CBS blades, and SPME-PESI probes and SPME-liquid chromatography-MS (SPME-LC-MS) for the analysis of drugs of abuse using the same MS instrument. Furthermore, for the first time, we developed different desorption chambers for MOI-MS for coupling with SPME fibers, CBS blades, and SPME-PESI probes, thus illustrating the universality of this approach. In total, eight analytical methods were developed, with the experimental data showing that all the SPME-based methods provided good analytical performance with R2 of linearities larger than 0.9925, accuracies between 81% and 118%, and good precision with an RSD% ≤ 13%.